Pengaruh partikel filler terhadap modulus elastisitas resin komposit Effect of filler particles on the elastic moduli of resin composites - Veni Takarini; Nina Djustiana; Renny Febrida (Journal of Dentomaxillofacial Science, 2012)
Modulus of elasticity is one of the mechanical properties of composite resins affects the resistance to deformation,the strength of bonding with tooth structure and wear resistance. Modulus of elasticity is determined by the volumefraction of filler particles as the inorganic phase composite resin. This literature study aims to evaluate the size,shape and type of filler particles that affect the modulus of elasticity for composite resin. In a constant volumefraction, the larger size of filler material tends to make more rigid while irregular shape of particles produceshigher modulus of elasticity than spherical form of particles. In addition, the type of filler particles also determinesthe modulus of elasticity for resin composite, such as silica as the main type of filler particles will enhance themodulus of elasticity whereas zirconium can result in a higher stiffness. In order to get composite resin restorationwith appropriate modulus of elasticity the necessary knowledge about the effect of different filler particle isrequired.